Skenario Konservasi Tanah pada Perkebunan Sawit sebagai Upaya Mitigasi Limpasan Permukaan pada DAS Arui, Kabupaten Manokwari, Papua Barat - Mahmud Mahmud (Institut Pertanian Bogor, 2023)
Indonesia, a country with high forest and land potential for economic growth, still relies on utilizing these two potentials. This study aims to create a conservation scenario in palm oil plantations that are expected to be able to mitigate surface runoff. The data collected include hydrology, land, area of oil palm plantations, and topography, which were analyzed based on threats and potential conservation that can be applied. Conservation scenarios that need to be carried out are: deadlock alley ditch (dad), mixed tree and palm oil plantations, planting oil palm without land cultivation, and immersing mulch. The simulation results of the dad design, if it rains heavily, all of the rainwater in the palm oil fields can be accommodated without a runoff. Mixed tree and oil palm plants are expected to maintain the availability of nutrients, increase the income of oil palm smallholders, and have a good impact on soil fertility. Planting oil palm without land cultivation is expected to reduce surface runoff, increase water infiltration into the soil, and expand water catchment areas. The immersion of palm mulch is expected to help retain soil moisture, add nutrients, enhance the soil's ability to absorb water, and prevent erosion. Conservation scenarios in the long term, such as dad, mixed tree and oil palm plantations, oil plantations without land cultivation, and mulch immersion, are expected to be able to mitigate flooding. Keywords: Arui watershed, conservation scenario, mitigation, oil palm, surface runoff